Pleiotropic Effects of Heparins: From Clinical Applications to Molecular Mechanisms in Hepatocellular Carcinoma. (22nd October 2018) - Korhan, Peyda; Yılmaz, Yeliz; Bağırsakçı, Ezgi; Güneş, Ayşim; Topel, Hande; Carr, Brian I.; Atabey, Neşe
Abstract : Hepatocellular carcinoma (HCC) is a major health problem worldwide and most cases are incurable because of late presentation. It is the most common primary neoplasm of the liver and often arises in the context of a chronic liver disease that impairs coagulation. Portal vein thrombosis (PVT) is a common complication of HCC that is associated with a poor prognosis. Heparin derivatives are widely used in the management of venous thromboembolism (VTE). Among them low molecular weight heparin (LMWH) favorably influences the survival in patients with advanced cancer, including HCC. Due to their pleiotropic function, heparins affect tumorigenesis in many ways and may promote or hamper tumorigenic transformation depending on the cancer type and cancer stage along with their structural properties and concentration. Thus, their application as an antithrombotic along with the conventional therapy regime should be carefully planned to develop the best management strategies. In this review, we first will briefly review clinical applications of heparin derivatives in the management of cancer with a particular focus on HCC. We then summarize the state of knowledge whereby heparin can crosstalk with molecules playing a role in hepatocarcinogenesis. Lastly, we highlight new experimental and clinical research conducted with the aim of moving towards personalized therapy in cancer patients at risk of thromboembolism.